First Immunodetection of Sensory and Nervous Systems of Parasitic Larvae (Glochidia) of Freshwater Bivalve Nodularia douglasiae - Nikishchenko, Viktoria E.; Sayenko, Elena M.; Dyachuk, Vyacheslav A. (Frontiers in Physiology, 2022)
Most freshwater mussels have an unusual life cycle that requires host fish species for larval (glochidia) development and dispersal. Glochidia have a unique morphological structure that adapts to parasitic lifestyles and survival. The morphology of the glochidial shells of most Unionoidea, a group of freshwater bivalve mollusks, has been studied in detail using light and scanning electron microscopy. This study summarizes our data on the glochidia shell morphology of the Asian mussel Nodularia douglasiae from two localities in the Primorsky Territory, the Russian Far East. In contrast to the shell morphology of glochidia, little is known about the neurodevelopment of the Unionoidea. Herein, we first demonstrate that the structures of the sensory, muscle, and nervous systems of the glochidia larvae of N. douglasiae differ dramatically from those of the comparable larval systems of marine bivalve species, as revealed through alpha-acetylated tubulin, serotonin (5-HT), and FMRFamide antibodies as well as phalloidin for detection of F-actin and whole-mount confocal microscopy. We found that the glochidia sensory system included four pairs of tubulin-lir multicilia hair cells. Non-ciliar tubulin-lir cells synthesize the neuropeptide FMRFamide and are identified as afferent neurons collecting information from peripheral tubulin-lir hair sensory cells to nervous regulators. The glochidia’s muscular system was represented by a smooth adductor, retractors, and minor muscle bundles associated with the shell and visceral organs. The 5-HT-lir larval system is arranged most simply and consists of two immunopositive neurons innervating the adductor. The FMRFamide-lir system is more complicated and consists of several neuronal centers comprising neuronal bodies and their neurites in different areas of the larva. The FMRFamide-lir neurons are closely associated with sensory hair cells, and others, together with 5-HT-lir neurons, may be involved in the anlagen of adult ganglia. Thus, the nervous system of N. douglasiae glochidia is drastically different from other mollusks and lophotrochozoans because of the absence of an apical organ and the location and composition of FMRFamide and 5-HT cells. Morphological, molecular, and behavioral investigations of Unionoidea taxa need to be further conducted to investigate the parasite-host relationship, nerve-dependent regulation of parasite behavior, and evolution of mollusks.